Perubahan Beberapa Sifat Fisika dan Hasil Kacang Tanah akibat Pemberian Bahan Organik dan Pupuk Fosfat - Helmi Helmi (Jurnal Agrista, 2008)
Changes of Physical Properties of Entisols and Yield of Peanut Affected by Organic Matter and Phosphate FertilizerABSTRACT. A plot experiment was conducted in the field which objective was to study the effect of organic matter and phosphate fertilizer application on the change of physical properties of entisols and yield of peanut. Experimental treatment were arranged in the block random factorial design. There kinds of organic matter were animal manure, rice straw and peanut straw. The first factor were 0 ton ha-1 of organic matter, 20 ton ha-1 of animal manure, 20 ton ha-1 of rice straw and 20 ton ha-1 of peanut straw, the other factor was SP-36 dosage; there were 0, 60, and 120 kg ha-1. Each treatment was replicated three times. The result showed that organic matter and SP-36 application influenced to physical properties of Entisols i.e. decreased soil bulk density, increased total of soil porosity, available water porosity, soil aggregate stability index, soil aggregation and dry legume weight ha-1. The applications of 20 ton rice straw ha-1 was the optimum dosage on the application of 108.50 kg of SP-36 ha-1, with the maximum dry legume yield of 3.02 ton ha-1.